Investigating Current Delivery Vehicles for Efficient and Targeted Delivery of Therapeutic RNA and Future Perspectives Part A - Investigating current delivery vehicles for efficient and targeted delivery of therapeutic RNA and future perspectives/ Part B - The development of novel polymeric nanoparticles as efficient non-viral RNA delivery vectors - Sachan, Isha (2023)
Part A: The development of efficient nucleic acid delivery systems is a critical aspect of modern biomedical research aimed at harnessing the potential of gene therapy. Whilst nucleic acid-based therapies have shown success in the biomedical field, they face several key limitations that restrict their effectiveness as therapeutics. A major challenge is the efficient delivery of nucleic cargo to target tissues and cells. Due to nucleic acids being large, negatively charged molecules, they face barriers such as poor cellular uptake, degradation and endosomal escape. Overcoming these challenges to achieve efficient delivery is vital for therapeutics success. Prominent delivery systems such as lipid nanoparticles, polymer nanoparticles, and polyplexes show promise in surpassing these limitations, alongside the therapeutic potential of messenger-RNA and antisense oligonucleotides compounded with primarily lipid nanoparticles. Further research into overcoming the limitations is displayed through hypotheses of the use of polymer micelles and the proton sponge effect. Overall, this paper aims to provide a comprehensive overview of current successful delivery systems, recent advancements, and further novel methods to overcome the delivery limitations. Understanding of the strengths and limitations of these systems alongside the emerging approaches can be optimised by researchers to further their design and foster the translation of nucleic acid-based therapies into clinical practise, ultimately providing a route for the development of treatments for a plethora of diseases.